Gambaran Motivasi Salat pada Mahasiswa Fakultas Dakwah dan Komunikasi UIN Ar-Raniry Banda Aceh: Studi Fenomenologi Transendental Berdasarkan Self-Determination Theory - Cut Dahayani; Mahdi Nk; Syaiful Indra (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Students' motivation to perform salat (Islamic prayer) is influenced by various experiences that shape their awareness and commitment to worship. This study aims to explore the lived experiences of students at the Faculty of Da'wah and Communication, UIN Ar-Raniry Banda Aceh, in understanding their motivation to perform salat based on Self-Determination Theory using a transcendental phenomenological approach. This study employed a qualitative research method with a transcendental phenomenological approach. Six students were selected as participants through purposive sampling. Data were collected through in-depth interviews and observations and were analyzed using the stages of transcendental phenomenological analysis. The findings revealed two major themes: intrinsic motivation and extrinsic motivation. Intrinsic motivation was reflected in participants' awareness of obeying Allah SWT, fulfilling their spiritual needs, attaining inner peace, and improving the quality of their worship. Meanwhile, extrinsic motivation was shaped by family habituation, peer support, and Islamic preaching media, all of which strengthened their consistency in performing salat. The findings indicate that motivation to perform salat develops through the internalization of religious values, with external factors serving as reinforcing influences, while intrinsic motivation functions as the primary driving force for sustaining worship. This study extends the application of Self-Determination Theory within the context of Islamic worship and provides implications for the development of Islamic Guidance and Counseling services and religious development programs in higher education institutions.